Pengaruh Konsep Diri Siswa Terhadap Motivasi Belajar - Srumangestu, Novita Dwi (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2022)
The background in this study is about how the form of self-concept in students is there is an influence on student learning motivation which in this era of development in the world of education experiences various obstacles or problems, the breadth of these obstacles makes it difficult to predict what will happen. This study aims to determine the effect of two variables, namely the influence of self-concept on student motivation in class X SMA N 1 Weleri. This study uses a simple linear regression analysis method using a quantitative design. The sample used in this study was 105 students taken from 4 classes. The data was taken using the technique of giving a questionnaire through the Likert scale measurement in the form of a checklist on the research instrument. The results showed that the level of influence between self-concept on the learning motivation of class X students at SMA N 1 Weleri showed statistical data with the acquisition of a simple regression test that was carried out showing that the calculated F value was 67.616 with a significance level of 0.000 <0.05, the regression model can be used to predict the self-concept variable or in other words there is an influence of the self-concept variable (X) on the learning motivation variable (Y). For how strongly influenced between variables X and Y variables, it can be seen from the R Square value (determinant coefficient) of 0.396, which means that the influence of self-concept on learning motivation is 39.6%. So it can be seen that H0 is rejected and Ha is accepted, which means that there is an influence between self-concept on the learning motivation of class X students of SMA N 1 Weleri. Keywords: Self-Concept, Learning Motivation, Student